Character Education Value in the Ngendar Tradition in Piodalan at Penataran Agung Temple - Kadek Widiastuti; Heny Perbowosari (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
The ways to realize the generation which has a character can be apply in the social education through culture values, social ideology and religions, there are in Ngendar’ traditions that was doing by the children’s in Banjar Sekarmukti, Pangsan Village, Petang District, Badung regency. The purpose of this research to analyze the character values from Ngendar tradition. The types of this research are qualitative which ethnographic approach is. These location of this research in Puseh Pungit temple in Penataran Agung areal, Banjar Sekarmukti, Pangsan Village. Researcher using purposive sampling technique to determine information, collecting the data’s using observation, interviews, literature studies and documentation. The descriptive qualitative technique’ that are use to data analyses. The result of this research to show; first is process of Ngendar as heritage that celebrated in six months as an expression about grateful to the God (Ida Sang Hyang Widi Wasa). The reasons why these traditions’ always celebrated by the children’s are affected from holiness, customs and cultures. Second, Ngendar on the naming the characters which is as understanding character children’s with their religion that are affected by two things, the naming about religion behavior with way reprimand and appreciation through their confidence (Sradha) and Karma Phala Sradha. Next function is to grow their awareness. There are awareness that growed on their souls is to practice Ngendar traditions’, as awareness conscience, have an empathy and love the kind. The third function is in Ngendar tradition was happened on the actualizations those appearance of the habits to doing kindness, actualizations appearances on their social activities and actualization attitude. The third result from the implication education character value were has in Ngendar tradition that do by the children’s is implication religious value, implication honest value, implication discipline value, implication awareness environment value and implication the responsibilities.